Characterization of binabak, steamed mixture f freshwater prawn (Macrobrachium rosenbergii) and coconut meat (Cocos nucifera), from Pandan, Antique. - Malabanan, Shanel Ambay
Binabak is a steamed mixture of freshwater prawn (Macrobrachium rosenbergii), coconut meat (Cocos nucifera), onion (Allium cepa), garlic (Allium sativum L.), ginger (Zingiber officinale (Rosc)), and batuan (Garcinia morella) leaves popular in Pandan, Antique. The product is packed in hagikhik (Phrynium interruptum) leaves. The sensorial properties, physical and chemical properties, proximate composition, and microbiological quality of the binabak were studied. Its brief history and production in Pandan, Antique were documented. Its acceptance in locality outside Antique, was determined. Binabak production was initiated by Ciriaco Evangelio Antaran and Dolores Bancal Awayan in 1945. Currently fifteen (15) individuals carry out home scale production of binabak and sell the product in Pandan, Antique. The current processing involves six steps: raw material procurement, washing and peeling, size reduction, pounding, packing, and steaming. The mean weight, length, width, and thickness of the product were 42.29 grams, 4.46 inches, 1.49 inches, and 0.55 inches respectively for the product with packaging and 34.09 grams, 4.32 inches, 1.42 inches, and 0.42 inches respectively for the product without its packaging. The mean pH of the binabak was 6.93. The proximate analyses showed that the moisture content, fat, fiber, protein, ash and carbohydrates in the binabak sample were 66.94%, 14.78%, 0.29%, 0.483%, 4.99%, and 12.52% respectively. The binabak had a mean mesophilic count of 600 CFU/g which was less than 105 CFU/g, the recommended microbial limit for cooked meat products by Centre of Food Safety (2014). The mean Eschirichia coli count of the product which was 120.275 MPN/g was lower than the recommended rejection level 500 MPN/g for frozen cooked crustaceans by Food and Drug Administration (2013). Binabak was therefore safe for consumption. The consumer testing in Miagao, Iloilo revealed that the acceptance rating of the binabak was ?like very much? with a median score of 8. About eighty seven percent (87%) of the respondents rated the sample as like moderately to like extremely. Results suggested that the product can have high acceptability in other localities outside Pandan, Antique.